Cash, hoarding and the underground economy - Michael Pickhardt; Jordi Sardà (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2011)
We further refine the Modified-Cash-Deposits-Ratio (MCDR) approach, developed by Pickhardt and Sardà (2011, 2012) with a view to analyze size and causes of the cash using section of the underground economy. Among other things, we address the issue of cash hoarding. Findings include that the size of hoarded currency in Germany, about 40 to 110 billion Euro in 2009 according to recent estimates, may have reduced the size of the cash using underground economy in Germany, ceteris paribus, from about 8.5 to 2 percent in 2009, according to the MCDR approach.
Keywords: O17; H26; 330; underground economy; shadow economy; hoarding; cash demand; Schattenwirtschaft; Geldnachfrage; Schätzung; Deutschland